Multiple‐Robot Simultaneous Localization and Mapping: A Review. Issue 1 (30th July 2015) - Saeedi, Sajad; Trentini, Michael; Seto, Mae; Li, Howard
Abstract : Simultaneous localization and mapping (SLAM) in unknown GPS‐denied environments is a major challenge for researchers in the field of mobile robotics. Many solutions for single‐robot SLAM exist; however, moving to a platform of multiple robots adds many challenges to the existing problems. This paper reviews state‐of‐the‐art multiple‐robot systems, with a major focus on multiple‐robot SLAM. Various issues and problems in multiple‐robot SLAM are introduced, current solutions for these problems are reviewed, and their advantages and disadvantages are discussed.